Art Therapy Penerapan Ekspresi Seni untuk catarsis Emosi pada Anak di Dusun Kaligintung Melalui Kegiatan Lukisan - Setyasto, Novi; Inayati, Ainy; Trianda, Okta; Putri, Salsabila Arya (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
This community service program aims to help children aged 5 to 13 years in Kaligintung Hamlet, Karangduren Village, Tengaran District, Semarang Regency in managing and expressing emotions through Visual Art Therapy. Emotions in children if not channeled properly can cause children to lose control of their emotions. This program involves 30 children with a visual art approach as a cathartic medium that allows children to express their feelings nonverbally. The method used included three stages: 1) educational sessions on good emotion management and emotion regulation, 2) Visual Art Therapy practice sessions in the form of painting on canvas, and 3) interactive sessions that encourage active participation of children. The activity was held on March 16, 2025 in Kaligintung Hamlet, which has strong ties to art and culture. The results of the program showed high enthusiasm from the participants and positive changes in the short term regarding the understanding of emotion regulation. The program not only helped the children in developing the ability to manage emotions, but also trained creativity, built self-confidence, and strengthened their attachment to inherited local cultural values. The evaluation of the activity was conducted by taking into account the level of participation, understanding of emotion regulation, and changes before and after the activity with the contribution of a psychologist in each stage of the activityactivity.